2005
DOI: 10.1159/000088705
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Frailty

Abstract: Background: Frailty represents a body-wide set of a linked deterioration that occurs with ageing, but is susceptible to active intervention and is reversible. The concept of frailty should include broader environmental factors. A quantitative measure of frailty, the frailty index (FI), developed for elderly Canadians and shown to be valid for an elderly Chinese population, was examined for its association with socioeconomic, lifestyle, and social support network factors in an elderly Chinese cohort. Objective:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
195
4
28

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(241 citation statements)
references
References 27 publications
14
195
4
28
Order By: Relevance
“…12 According to Morley,39 poor social conditions worsen the physiopathology of the syndrome of frailty. This statement corroborated the findings of Woo,40 who reported that an individual´s social support network (appropriate interventions) is a modifying factor for frailty.…”
Section: Discussionsupporting
confidence: 89%
“…12 According to Morley,39 poor social conditions worsen the physiopathology of the syndrome of frailty. This statement corroborated the findings of Woo,40 who reported that an individual´s social support network (appropriate interventions) is a modifying factor for frailty.…”
Section: Discussionsupporting
confidence: 89%
“…23 In the present study, only 7% of the subjects who were considered to be frail did not have any chronic disease, and 25% of this group reported having hypertension. The frail group attended more medical visits than the non-frail group.…”
Section: And 87% In Belocontrasting
confidence: 51%
“…For example, an individual's wealth and the level of neighbourhood deprivation impacts on frailty and mortality but the size and direction of the impact may differ between the sexes (Gu et al, 2009;Lang et al, 2009;Major et al, 2010;Romero-Ortuno, 2014;Woo et al, 2005). Factors such as marital status, education level and social supports have all been reported to impact on male and female frailty (Andrew et al, 2008;Gorman and Read, 2006;Gu et al, 2009;Szanton et al, 2010;Woo et al, 2005).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%